STUDI KEPEMIMPINAN MUHAMMAD AL-FATIH DALAM BUKU MUHAMMAD AL-FATIH SANG PENAKLUK KONSTANTINOPEL KARYA JOHN FREELY - Mulyadi , Zulkifli (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2021)
Leadership is an important component which could not be separated from human life. One of the success leaders in history of Islamic civilization was Muhammad Al-Fatih. He managed to conquer Constantinople by such brilliant strategies. The purpose of this research is to find out: 1) The leadership character of Muhammad Al-Fatih; 2) Muhammad Al-Fatih's leadership style; 3) Relevance of the value of Muhammad Al-Fatih's leadership. This research includes qualitative research with a library study approach. The data source is taken from various literature related to Muhammad Al-Fatih. The research procedure used is to search various literature, read, filter, and mark the processed parts into the report. Based on the analysis, researchers can conclude that Muhmmad Al-Fatih’s leadership which can be modelled especially for the young generation. Moreover, Indonesia will get demographic bonus that must be utilized as well for a better development. This conclusion is strengthened by some specific conclusions, those are: 1) Muhammad Al-Fatih was a Muslim leader who always had the reason behind his actions; 2) Muhammad Al-Fatih has charisma in leading his army; 3) Good character and charismatic leadership style are very relevant to apply in this day and age. Keywords: Character, Leadership, Relevance.